OS10.2 Effectiveness and tolerability of lacosamide as add-on therapy in patients with brain tumor-related epilepsy: results from a prospective, non-interventional study in European clinical practice - Rudà, R (Neuro Oncol, 2019)
BACKGROUND: Data on the use of lacosamide (LCM) for the treatment of brain tumor-related epilepsy (BTRE) are limited. The objective of this study was to evaluate the effectiveness and tolerability of LCM added to 1 or 2 antiepileptic drugs (AEDs) in the treatment of patients with epilepsy due to low-grade primary brain tumor. MATERIAL AND METHODS: Prospective, multicenter, single-arm, non-interventional study with a 6-month observation period (EP0045; NCT02276053). LCM was added to existing treatment with 1 or 2 AEDs. Patients aged ≥16 years with BTRE secondary to low-grade glioma (WHO Grade I-II) were eligible. Primary endpoints: patients experiencing a ≥50% reduction in seizure frequency from Baseline to Month 6; Patient’s Global Impression of Change (PGIC) rating at Month 6. Secondary endpoints: Kaplan-Meier estimated retention rate and change from Baseline in quality-of-life to Month 6 (EQ-5D-5L and MDASI-BT). Safety variables: occurrence of adverse drug reactions (ADRs) and ADRs leading to discontinuation. The present analysis was performed for the safety set: all patients who took ≥1 dose of lacosamide. RESULTS: The study was conducted between November 2014 and December 2017. Patients were enrolled from 24 sites in Italy, the United Kingdom, the Netherlands, Germany, France, and Spain. 93 patients started LCM (mean [SD] age: 44.5 [14.7] years; 50 [53.8%] male); 14 (15.1%) withdrew from the study by 6 months. 85 (91.4%) patients had low-grade glioma, 3 (3.2%) had suspected glioma, 3 (3.2%) had meningioma, 1 (1.1%) had craniopharyngioma, and 1 (1.1%) had a histologically unverified tumor. At 6-months, 66 (71.0%) patients reported a ≥50% reduction in seizure frequency, 30 (32.3%) of whom were seizure-free. Improvements on PGIC were reported by 49 (52.7%) patients. The Kaplan-Meier estimated 6-month retention rate was 86.0%. Quality of life (EQ-5D-5L) and symptoms outcome measures (MDASI-BT) remained stable. ADRs leading to discontinuation occurred in 4 (4.3%) patients, most commonly vertigo (2 [2.2%] patients). CONCLUSION: This is the first prospective, multicenter study focusing on epilepsy due to slow-growing tumors (mainly low-grade gliomas), treated with LCM. The results suggest that LCM reduces seizures in patients with resistant BTRE. The majority of patients noticed a clinical improvement with the addition of LCM. Observed ADRs were consistent with the known safety profile of LCM. STUDY SUPPORTED BY: UCB Pharma.